2014
DOI: 10.1016/j.ophtha.2013.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Geographic Atrophy in the Comparison of Age-related Macular Degeneration Treatments Trials

Abstract: Purpose To describe risk factors for geographic atrophy (GA) in the Comparison of Age-related Macular Degeneration Treatments Trials (CATT). Design Cohort within a randomized clinical trial. Participants We analyzed 1024 CATT patients with no GA visible on color fundus photographs (CFPs) and/or fluorescein angiograms (FAs) at enrollment. Methods Eyes were assigned to ranibizumab (0.5 mg) or bevacizumab (1.25 mg) treatment and to a 2-year monthly or pro re nata (PRN) injection regimen, or monthly injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
396
4
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 492 publications
(415 citation statements)
references
References 28 publications
8
396
4
7
Order By: Relevance
“…At present, the underlying cause of this finding remains unclear. Findings on the progression of heredodegenerative retinal disease, in particular age-related macular degeneration, or toxic retinopathy have shown that the functional capacity of a stressed pigment epithelium -and hence the receptors -remains intact for a limited time and is followed by atrophy [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the underlying cause of this finding remains unclear. Findings on the progression of heredodegenerative retinal disease, in particular age-related macular degeneration, or toxic retinopathy have shown that the functional capacity of a stressed pigment epithelium -and hence the receptors -remains intact for a limited time and is followed by atrophy [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…4 This could lead to overtreatment with subsequent increase of associated risks such as chorioretinal atrophy. 5 Even though larger prospective trials are needed to elucidate on the best treatment protocol, they are difficult to arrange due to the rarity of the condition. Sir, A rapidly emerging ocular zoonosis; Dirofilaria repens Dirofilariasis-commonly caused by Dirofilariasis repens and D. immitis and transmitted via mosquito bites-is a roundworm zoonosis that is emerging as a public health concern in Eastern and Southern Europe, Asia Minor, Central Asia, and Sri Lanka, possibly due to climatic changes.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…This revision would align the UK screening protocol with the current American Academy of Pediatrics/American Academy of Ophthalmology/ American Association of Pediatric Ophthalmology and Strabismus recommendation for 22-27 weeks GA infants to initiate screening at 31 PMA. 5 Data from other neonatal units in the UK are needed to add confidence to this suggestion.…”
mentioning
confidence: 99%
“…4 This could lead to overtreatment with subsequent increase of associated risks such as chorioretinal atrophy. 5 Even though larger prospective trials are needed to elucidate on the best treatment protocol, they are difficult to arrange due to the rarity of the condition.…”
Section: Sir Intravitreal Aflibercept For Choroidal Neovascularisatimentioning
confidence: 99%